1998
DOI: 10.1074/jbc.273.1.315
|View full text |Cite
|
Sign up to set email alerts
|

The Jak/Stat Pathway and Urokinase Receptor Signaling in Human Aortic Vascular Smooth Muscle Cells

Abstract: The binding of urokinase plasminogen activator (uPA) to its specific receptor (uPAR) facilitates migration of vascular smooth muscle cells (VSMC). However, the signaling cascade utilized by the urokinase receptor is only incompletely understood. We investigated intracellular uPA/uPAR signaling in human aortic VSMC from the cell membrane to the nucleus. uPA binding to VSMC induced a rapid and pronounced increase in tyrosine phosphorylation of several proteins with molecular masses of 53-60, 85-90, and 130 -140 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
111
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(120 citation statements)
references
References 33 publications
(38 reference statements)
7
111
0
2
Order By: Relevance
“…uPAR also appears to associate with ␤ 2 integrins and members of the Src family of kinases (44,45). In vascular smooth muscle cells, uPAR was associated with JAK1, Tyk2, and Src kinases (46), whereas in kidney epithelial tumor cells, uPAR associates with gp130 and JAK1 (47).…”
Section: Discussionmentioning
confidence: 99%
“…uPAR also appears to associate with ␤ 2 integrins and members of the Src family of kinases (44,45). In vascular smooth muscle cells, uPAR was associated with JAK1, Tyk2, and Src kinases (46), whereas in kidney epithelial tumor cells, uPAR associates with gp130 and JAK1 (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, some data suggest that signaling and activation of a chemotactic and proliferative program may take place upon interaction of u-PAR with a truncated form of u-PA, lacking the catalytic site, or in the presence of inhibitors of plasmin generation. 19,27,42,51,52 Furthermore, it has been shown that u-PAR, which is spatially located in focal contacts and at the leading edge of migrating cells, 53,54 may directly interact via its extracellular domain with activated integrins promoting adhesion and migration toward specific matrix proteins even in the absence of u-PA. 55 Thus, the potential biological interactions of the u-PA/u-PAR system appear more complex than expected and require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…u-PA/u-PAR promotes cell/cell and cell/ECM proteolysis by regulating localised plasminogen activation . Independent of proteolysis, u-PA enhances cell invasion through activation of several migration-associated signalling molecules such as extracellular signal-regulated kinases (Nguyen et al, 1998), focal adhesion kinases (Tang et al, 1998) and signal transducers and activators of transcription 1 (STAT1) (Dumler et al, 1998). Such intercellular signal transduction is apparently facilitated by the interaction of u-PAR with integrins (Wei et al, 1996;Degryse et al, 2001) and cytoskeletal components (Xue et al, 1997).…”
mentioning
confidence: 99%